AGNs with discordant optical and X-ray classification are not a physical family: diverse origin in two AGNs. Issue 1 (8th April 2017) - Ordovás-Pascual, I.; Mateos, S.; Carrera, F. J.; Wiersema, K.; Barcons, X.; Braito, V.; Caccianiga, A.; Del Moro, A.; Della Ceca, R.; Severgnini, P.
Abstract: Approximately 3–17 per cent of active galactic nuclei (AGNs) without detected rest-frame UV/optical broad emission lines (type-2 AGN) do not show absorption in X-rays. The physical origin behind the apparently discordant optical/X-ray properties is not fully understood. Our study aims at providing insight into this issue by conducting a detailed analysis of the nuclear dust extinction and X-ray absorption properties of two AGNs with low X-ray absorption and with high optical extinction, for which a rich set of high-quality spectroscopic data is available from XMM–Newton archive data in X-rays and XSHOOTER proprietary data at UV-to-NIR wavelengths. In order to unveil the apparent mismatch, we have determined the A V / N H and both the supermassive black hole and the host galaxy masses. We find that the mismatch is caused in one case by an abnormally high dust-to-gas ratio that makes the UV/optical emission to appear more obscured than in the X-rays. For the other object, we find that the dust-to-gas ratio is similar to the Galactic one but the AGN is hosted by a very massive galaxy so that the broad emission lines and the nuclear continuum are swamped by the star light and difficult to detect.